Joint BSPGHAN and Coeliac UK guidelines for the diagnosis and management of coeliac disease in children. Issue 10 (28th August 2013) - Murch, Simon; Jenkins, Huw; Auth, Marcus; Bremner, Ronald; Butt, Assad; France, Stephanie; Furman, Mark; Gillett, Peter; Kiparissi, Fevronia; Lawson, Maureen; McLain, Bruce; Morris, Mary-Anne; et al.
Abstract : The revised BSPGHAN guidelines for the diagnosis and management of coeliac disease represent an important shift in diagnostic strategy, aimed at simplifying and shortening the diagnostic process in selected cases. Guidance is given concerning the indications for testing for coeliac disease, which is still significantly underdiagnosed in the UK. While screening data suggest a likely incidence of 1 in 100 persons, only 10%–20% of this figure is currently being diagnosed.The BSPGHAN guidelines follow the new ESPGHAN guidelines in overall diagnostic strategy, while providing more didactic stratagems, which should be of assistance for paediatricians in specialties other than gastroenterology.